Tok tekočine skozi reže v hidravličnih sestavinah - Pezdirnik, Jože (Strojniški vestnik, 2001)
The paper gives a derivation of an equation for calculating the amount the leakage flow through gaps in the components of a power-control hydraulics system. In deriving the equation some simplifications were adopted, these are also stated in other reports that mostly give final equations only for the calculation of the fluid leakage flow through gaps. In some cases, where the eccentricity of the piston position against the borehole is considered, these equations are wrongly written for the part that considers the eccentricity. Besides a somewhat different derivation than presented in 1, this paper also gives an evaluation of the exactness of the mathematical formulation for changing the gap size by the circumference of the circular cross-section-shaped spool at the eccentric position in the borehole with a circular cross-section shape, too. There is a very small laxity between both elements. ...
Keywords: reže; ohlapi; puščanje; bati; izvrtine; hidravlični sistemi